2010
DOI: 10.5194/acp-10-10621-2010
|View full text |Cite
|
Sign up to set email alerts
|

Peroxy radical partitioning during the AMMA radical intercomparison exercise

Abstract: Abstract. Peroxy radicals were measured onboard two scientific aircrafts during the AMMA (African Monsoon Multidisciplinary Analysis) campaign in summer 2006. This paper reports results from the flight on 16 August 2006 during which measurements of HO 2 by laser induced fluorescence spectroscopy at low pressure (LIF-FAGE) and total peroxy radicals (RO * 2 = HO 2 + RO 2 , R = organic chain) by two similar instruments based on the peroxy radical chemical amplification (PeRCA) technique were subject of a blind in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 46 publications
(56 reference statements)
2
33
0
Order By: Relevance
“…3.3. There is no information available about the relative distribution of peroxy radicals during AMMA except for the radical intercomparison exercise (Andrés Hernández et al, 2010) where the HO 2 /RO 2 ratio remained close to 1:1. Complementary modeling results indicated that CH 3 O 2 represents 90% of the alkyl peroxy radicals present .…”
Section: Error Analysis and Detection Limitmentioning
confidence: 99%
“…3.3. There is no information available about the relative distribution of peroxy radicals during AMMA except for the radical intercomparison exercise (Andrés Hernández et al, 2010) where the HO 2 /RO 2 ratio remained close to 1:1. Complementary modeling results indicated that CH 3 O 2 represents 90% of the alkyl peroxy radicals present .…”
Section: Error Analysis and Detection Limitmentioning
confidence: 99%
“…The square root of the Allan variance, termed the Allan deviation, provides an indication of the instrument stability (Allan, 1966;Werle et al, 1993). The Allan deviation plots for each of the BBCEAS instrument's measurement channels are shown in Fig.…”
Section: Determination Of Detection Sensitivitiesmentioning
confidence: 99%
“…These gases are of interest due to their participation in a range of atmospheric processes: oxidation by NO 3 controls the lifetimes of some species, including a number of volatile organic compounds (VOCs) that are important for photochemical ozone production, while deposition of N 2 O 5 onto certain aerosol surfaces represents a potentially important but presently unquantified sink of diurnally aggregated NO x (Chang et al, 2011). The BBCEAS instrument is one of a suite of instruments on board the United Kingdom's BAe 146-301 Facility for Airborne Atmospheric Measurements (FAAM) research aircraft, which collectively provide comprehensive characterisation of a range of important trace gases and aerosol species (Pfister et al, 2006;Capes et al, 2009;Johnson et al, 2009;Lewis et al, 2007;Andrés-Hernández et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It applies chemical conversion of HO 2 to OH at reduced pressure and detects OH by LIF (see review, Heard and Pilling, 2003). Chemical conversion combined with radical amplification H. Fuchs et al: HO 2 by LIF: calibration and interference from RO 2 is used by Peroxy Radical Chemical Amplifier (PERCA) (Cantrell et al, 1984;Hastie et al, 1991;Clemitshaw et al, 1997;Burkert et al, 2001;Sadanaga et al, 2004;Mihele and Hastie, 2000;Green et al, 2006;Andrés-Hernández et al, 2010) and Peroxy Radical Chemical-Ionization Mass Spectrometry (ROxMas, PerCIMS) (Hanke et al, 2002;Edwards et al, 2003;Hornbrook et al, 2011), in order to achieve high measurement sensitivities for HO 2 . All indirect techniques (LIF, PERCA and ROxMas/PerCIMS) make use of the conversion reaction between HO 2 and NO, in order to produce OH.…”
Section: Introductionmentioning
confidence: 99%